Blood cell counting, identification, and grouping - Stevems, Ralph W.; McAvey, Russ.; Marquess, Janet L.; Wm. C. Brown Publishers (Dubuque, Iowa : Wm. C. Brown, 1990)
Designed to help students learn the basics of counting and identifying cells found circulating in the blood, and determine the hematic group and type of the blood sample.
Thais Weibel
VHS
Keywords: Blood cells count; Blood -- Examination; Blood cells; Blood groups